Effectiveness of Law No. 40 of 1999 on the press (study of the journalistic code of ethics on reporting that triggers conflict in society) - Yulianto, Yoga Farhan; Suharso, Suharso; Sintha Dewi, Dyah Adriantini; Syafingi, Habib Muhsin; Budiharto, Budiharto (Universitas Muhammadiyah Magelang, 2021)
In an effort to support the success of Indonesia's development, arrangements are needed for all supporting elements. One of them is the regulation of press activities, namely through Law Number 40 of 1999 concerning the Press and the Journalistic Code of Ethics which is regulated in Indonesia. This is because there are several reports that actually cause conflict in the community, such as the cases of Wamena, Ambon and Sampit. One of the causes of the conflict is due to overlapping regulations that are applied and there are still many shortcomings that cause uncertainty among law enforcers. This can be seen in the imposition of sanctions on journalists. There is no article in the journalistic code of ethics that authorizes any group outside PWI to take action against an Indonesian journalist or against press publications. This study aims to analyze the effectiveness of Law No. 40 of 1999 concerning the press and the Enforcement of the Journalistic Code of Ethics against news that triggers conflict in society. This research is a normative legal research using the Statute Approach and the case approach. The results of the study show that Law Number 40 of 1999 concerning the Press and the Journalistic Code of Ethics has not been implemented optimally or effectively, because there are still shortcomings that cause uncertainty among law enforcement. One of the obstacles is because there is no certainty which party has the authority to take action against journalists who violate it but are outside the journalists' organization.